Floristic Diversity And Dynamics In The Farasan Islands, Red Sea, Saudi Arabia - Al-Mutairi, Khalid Awadh (2012)
The current work establishes the first intensive ecological study of Farasan Archipelago concerning the mechanisms and processes of vegetation diversity and composition. The floristic survey was carried out on 20 islands which vary in areas from few square meters to about 381 km2 to analyze the floristic diversity and composition. The analysis identified a total of 191 species belonging to 129 genera and 53 families, with 38 species belonging to the Monocotyledoneae and 153 species to the Dicotyledoneae.